ANALISIS TIMBRE RAPA’I BUATAN FAJAR SIDDIQ DI DESA KAYEE LHEU, KECAMATAN INGIN JAYA, KABUPATEN ACEH BESAR (KAJIAN MUSIK MULTIMEDIA) - Benny Andiko; Berlian Denada (Gorga : Jurnal Seni Rupa, 2021)
This research is entitled "Analysis of Timbre Rapa'i Made by Fajar Siddiq in Kayee Lheu Village, Ingin Jaya, Aceh Besar District. This study aims to determine the form of the Rapa'i timbre made by Fajar Siddiq, what are the steps for recording timbre and analyzing timbre using the Spectrum Analyzer on the PreSonus Studio One 5 software. Focusing on multimedia music studies, adopting the topic of recording stages with categories, namely; according to their nature and according to the sound system. The initial process of recording music is tracking. Timbre depends primarily on the acoustics of the stimulus, but also depends on the waveform. Timbre refers to the dimension of sound that allows the listener to identify the source of the sound and the content of the sound. Using a recording stage approach from Ambrosius Yuniart Lefaan and timbre analysis from Pratt and Doak. The research method used in this study is qualitative research as a research procedure that produces descriptive data in the form of written information and analysis results using a Spectrum Analyzer. Using the stages of data collection, namely: observation; literature review; interviews and documentation. The results and discussion of this research are; Rapa'i timbre which consists of four sound colors (dum, preng, breuk dan crik) recorded using digital recording equipment as follows; Audio Technica AT 2035 condenser microphone using ambient miking technique, Zoom R24 audio interface; multitrack recording technique with tracks separated from the four Rapa'i timbres; delivery media is a classification of membranophone namely Rapa'i; DAW (Digital Audio Workstation) storage media, namely PreSonus Studio One 5 software. The recording process with tracking stages uses four channels with mono audio recording type, 44.1 kHz sample rate with 24 bit resolution. The fundamental frequency is timbre dum 172Hz with SPL -17.8dB, preng 192Hz with SPL -16.8dB, breuk 172Hz with SPL -28.2dB and crik 192Hz with SPL -22.3 dB. Keywords: analysis, timbre, rapa’I, fajar, siddiq.AbstrakPenelitian ini berjudul “Analisis Timbre Rapa’i Buatan Fajar Siddiq di Desa Kayee Lheu, Ingin Jaya, Kabupaten Aceh Besar (Kajian Musik Multimedia). Penelitian ini bertujuan untuk mengetahui bentuk timbre Rapa’i buatan Fajar Siddiq, bagaimana tahapan perekaman timbre dan analisis timbre menggunakan Spectrum Analyzer pada software PreSonus Studio One 5. Memfokuskan pada kajian musik multimedia, mengadopsi topik bahasan tahapan perekaman dengan kategori yaitu: menurut sifatnya dan menurut peralatan tata suara. Proses awal rekaman musik yaitu tracking. Timbre tergantung terutama pada akustik stimulus, tetapi juga tergantung pada bentuk gelombang. Timbre mengacu pada dimensi bunyi yang memungkinkan pendengar mengindentifikasi sumber bunyi dan kandungan bunyi. Menggunakan pendekatan tahapan perekaman dari Ambrosius Yuniart Lefaan dan analisis timbre dari Pratt dan Doak. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif sebagai prosedur penelitian yang menghasilkan data deskriptif berupa informasi tertulis dan hasil analisis menggunakan Spectrum Analyzer. Menggunakan tahapan pengumpulan data yaitu: observasi; studi pustaka; wawancara dan dokumentasi. Hasil dan pembahasan dari penelitian ini yaitu; timbre Rapa’i yang terdiri dari empat warna bunyi (dum, preng, breuk dan crik) direkam menggunakan peralatan rekaman digital sebagai berikut; microphone condenser Audio Technica AT 2035 menggunakan teknik ambient miking, audio interface Zoom R24; teknik rekaman multitrack dengan track yang terpisah dari empat timbre Rapa’i; media penyampaian merupakan klasifikasi dari membranophone yaitu Rapa’i; media penyimpan DAW (Digital Audio Workstation) yaitu software PreSonus Studio One 5. Proses rekaman dengan tahapan tracking menggunakan empat channel dengan tipe rekam mono audio, sample rate 44.1 kHz dengan resolusi 24 bit. Frekuensi fundamental timbre dum 172Hz dengan SPL -17,8dB, preng 192Hz dengan SPL -16,8dB, breuk 172Hz dengan SPL -28,2dB dan crik 192Hz dengan SPL -22,3 dB.  Kata Kunci: analisis, timbre, rapa’I, fajar siddiq.  Authors:Benny Andiko : Institut Seni Budaya Indonesia AcehBerlian Denada : Institut Seni Budaya Indonesia Aceh References:Andiko, Benny. (2021). “Timbre Rapa’I”. Hasil Dokumentasi Pribadi: 12 September 2021, Desa Kayee Lheu.Bartlett, Bruce dan Jenny Bartlett. (2009). Practical Recording Techniques. Burlington: Elsevier.Ediwar. (2016). Rekonstruksi dan Revitalisasi Kesenian Rapa’I Aceh Pasca Tsunami. Resital, 17(1), 30-45.Huber, David. M. & Rustein, Robert. E. (2017). Modern Recording Techniques. Routledge: Focus Press.Lefaan, Ambrosius Yuniart. (2010). Studio Rekaman Musik di Yogyakarta. S1 Thesis. Yogyakarta: UAJY.Rossing, Thomas. D. (2002). The Science of Sound. Routledge: Focal Press. Rumsey, Francais. & McCormick, Tim. (2009). Sound and Recording: Applications and Theory (Audio Engineering Society Presents). Routledge: Focal Press.Sadiman, Arif. S. (2000). Peran Teknologi dalam Meningkatkan Mutu Pendidikan Dasar. Jakarta: Teknodik.Siddiq, Fajar. (2021). “Timbre Rapa’I”. Hasil Wawancara Pribadi: 12 September 2021, Desa Kayee Lheu.Technica, Audio. (2021). Cardioid Condenser Microphone AT2035. https://www.audio-technica.com/en-us/at2035 (diakses tanggal 7 Juli 2021).Walzer, Michael. (1997). On Toleration: Castle Lectures in Ethics, Politics, and Economics. Yale: University Press.Wijayanto. (2017). Analysis of Sound Pressure Level (SPL) and Lay Out of Engines in The Factory. Media Mesin, 8(1), 38-44.Zoomtech. (2021). Audio Interface Zoom R24. https://zoomcorp.com/en/us/digital-mixer-multi-track-recorders/multi-track-recorders/r24/ (diakses tanggal 7 Juli 2021).